Experience of the Chilean Judicial Power in the application of the Brasilia Rules - Cisternas Rocha, Lamberto (2020)
The Chilean Judicial Power, by approving the Brasilia Rules, has carried out multiple initiatives that seek to make the right of access to justice effective, with special emphasis on groups in vulnerable situations. This produced a cultural and institutional change that affects the jurisdictional work, which, although it concerns to the resolution of conflicts of legal relevance, can also help correct situations of discrimination and eliminate barriers that prevent some people fromfully enjoying of their fundamental rights.